Profitability determinants of five-star hotels in Yogyakarta - Kusumawati, Febriana Riestyaningrum (Annals of Management and Organization Research, 2020)
Purpose: This study aimed to investigate how customers' satisfaction, employee satisfaction, and service quality affect profitability. Research methodology: A total of 450 questionnaires were distributed, 424 were returned and a Partial Least Square (PLS) modeling technique was used to test the hypotheses. Results: The results of this study explain that customers' satisfaction and employee satisfaction play essential roles in enhancing profitability, service quality on customers' satisfaction, and employee satisfaction on customer satisfaction. Finally, there are no essential roles between service quality on profitability. Limitations: This study only used customer satisfaction, service quality, and employee satisfaction as the determinant of profitability. There may be other factors that affect profitability, such as perceived value and customer loyalty, that can be considered to determine which marketing strategy should be used as a practical contribution. Contribution: Therefore, based on the research, hotel management should build a favorable image on a long-term basis using identification and efficient management in terms of promise, positioning, personality, and people. This research implies that the hotel manager should continuously improve service quality and employee satisfaction, thus increasing customers' satisfaction, which will lead to profitability.